Peinture Belge Contemporaine. (Brussel : Ministerie van Nederlandse Cultuur - Dienst Kunstpropaganda Brussel, 1969)
Burssens Jan, Lahaut Pierre, Londot Louis-Marie, Mara Pol, Notebaert,Marcel, Roobjee Pjeroo, Roquet Maurice, Roulin Félix, Verheyen Jef, Verstockt Mark, Vlerick Pierre
Publication referring to the exhibition Belgian Contemporary Painting, Montréal, 12.06.1969-07.09.1969
Vermelding P. Vlerick [p. 22]
Schenking Pierre Vlerick
boek
Keywords: Burssens, Jan; Lahaut, Pierre